Pretreatment liquid for semiconductor substrate and preparation method thereof

By combining nanodiamond abrasives in the pretreatment liquid of the semiconductor substrate with a conductive hydrophilic coating, the problem of poor abrasive aggregation and dispersion is solved, and higher grinding accuracy and stability are achieved, as well as longer liquid stability.

CN119060692BActive Publication Date: 2025-04-04ZHONGJI SEMICON MATERIALS (SHENZHEN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411555928.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-04-04
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In the pretreatment liquid of semiconductor substrates, nano-level abrasives are prone to agglomeration, resulting in poor dispersion and affecting the processing effect.

Method used

Using a pretreatment liquid including nanodiamond abrasives, dispersants, pH adjusters, suspensions and polar solvents, the nanodiamond abrasives are coated with a conductive hydrophilic layer on the surface. The dispersion and stability of the abrasive are improved through specific formula ratios and preparation methods.

Benefits of technology

The conductive hydrophilic coating improves the conductivity and hydrophilicity of the abrasive, reduces electrostatic accumulation, prevents abrasive agglomeration, improves grinding accuracy and stability, and extends the storage life and stability of the pre-treatment liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060692B_ABST
    Figure CN119060692B_ABST
Patent Text Reader

Abstract

The present invention proposes a pretreatment liquid applied to a semiconductor substrate and a preparation method thereof, wherein the pretreatment liquid applied to the semiconductor substrate comprises: nano-diamond abrasive, dispersant, pH regulator, suspending agent and polar solvent, the nano-diamond abrasive is provided with a surface layer, the surface layer comprises a conductive hydrophilic coating, and calculated by weight percentage, the nano-diamond abrasive accounts for 0.1-2%, the dispersant accounts for 1-5%, the pH regulator accounts for 0.5-2%, the suspending agent is 0.5-3%, and the remainder is a polar solvent. The conductive hydrophilic coating of the nano-diamond particles forms a conductive coating on the surface of the nano-particles, improves the conductivity during the grinding process, and reduces the accumulation of static electricity. In particular, in the process of high-speed fine grinding, reducing static electricity can prevent particle agglomeration and improve grinding accuracy and stability. The conductive hydrophilic coating also makes the particles have better hydrophilicity, improving their dispersibility and stability in the solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor processing, and in particular relates to a pre-treatment liquid applied to a semiconductor substrate and a preparation method thereof. Background Art

[0002] In semiconductor devices, semiconductor substrate refers to the material base used to support and manufacture semiconductor devices, usually a wafer or substrate with a certain thickness and flatness. As the basic material for crystal growth, lithography, deposition and other processes in the manufacturing process of semiconductor devices, it is widely used in the production of integrated circuits, LEDs, micro-electromechanical systems (MEMS), radio frequency (RF) devices, etc. The selection of semiconductor substrate is very important because it directly affects the performance, reliability and production cost of the device. Common semiconductor substrate materials include silicon, gallium arsenide, silicon carbide, sapphire, diamond and other materials with high hardness.

[0003] In order to significantly reduce the surface roughness of semiconductor substrates and help obtain high-precision surface polishing effects, nano-scale high-hardness particles are selected as abrasives for pre-treatment processes such as grinding and polishing. However, nano-scale abrasives have extremely high specific surface areas, which makes the van der Waals force, electrostatic force and surface energy between particles more significant. Particles are prone to interact with each other, forming agglomerations, resulting in poor dispersibility. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a pretreatment liquid applied to semiconductor substrates and a preparation method thereof, aiming to solve the problem that abrasives are easy to agglomerate and have poor dispersibility in the pretreatment liquid.

[0005] To solve the above technical problems, the present invention is implemented as follows: a pretreatment liquid applied to a semiconductor substrate comprises: nano-diamond abrasive, a dispersant, a pH regulator, a suspending agent and a polar solvent, wherein the nano-diamond abrasive is provided with a surface layer, and the surface layer comprises a conductive hydrophilic coating. Calculated by weight percentage, the nano-diamond abrasive accounts for 0.1-2%, the dispersant accounts for 1-5%, the pH regulator accounts for 0.5-2%, the suspending agent is 0.5-3%, and the balance is the polar solvent.

[0006] In some embodiments of the present invention, the dispersant includes at least one of polyacrylic acid, polymaleic anhydride, acrylic acid / 2-propylene sulfonic acid copolymer, and polyacrylamide;

[0007] The pH regulator includes at least one of sodium hydroxide, potassium hydroxide, triethanolamine, and ammonia water;

[0008] The suspending agent includes at least one of hydroxyethyl cellulose, xanthan gum, carbomer and bentonite;

[0009] The polar solvent includes at least one of deionized water, ethanol, acetone and isopropanol.

[0010] The present invention provides a preparation method for preparing the pretreatment solution for semiconductor substrate as described above, the preparation method comprising the following steps:

[0011] S1, pretreating the nano-diamond raw material to obtain a nano-diamond abrasive;

[0012] S2, adding the nano-diamond abrasive into a polar solvent containing a dispersant and a pH adjuster in batches to obtain a mixed solution;

[0013] S3, adding a suspending agent to the mixed solution, performing ultrasonic dispersion, and obtaining a pre-treatment solution.

[0014] In some embodiments of the present invention, step S1 comprises:

[0015] S1.1. Place the nanodiamond raw material in a plasma chamber, evacuate the chamber, introduce oxygen, and start the plasma excitation source for activation treatment;

[0016] S1.2, transferring the activated nanodiamond raw material to an acid washing solution, and then washing, filtering and drying in sequence to obtain surface-modified nanodiamond particles;

[0017] S1.3, transferring the surface modified nano-diamond particles into a conductive hydrophilic coating solution, heating and stirring, and then performing a deposition and pulling process, and after drying and thermal curing, obtaining a nano-diamond abrasive with a conductive hydrophilic coating.

[0018] In some embodiments of the present invention, in step S1.1, the oxygen flow rate is 20-50 sccm;

[0019] In the step S1.2, the pickling solution includes a strong acid and hydrogen peroxide, the strong acid includes at least one of sulfuric acid, nitric acid, and hydrochloric acid, and the volume ratio of the strong acid to the hydrogen peroxide is 1:1-2;

[0020] In the step S1.3, the conductive hydrophilic coating solution includes at least one of carboxylated polyvinyl pyrrolidone, polyethylene glycol-modified polyaniline, and polyethylene glycol-modified polypyrrole.

[0021] In some embodiments of the present invention, the surface layer further comprises an antistatic hydrophilic coating disposed on the surface of the conductive hydrophilic coating;

[0022] After step S1.3, the method further includes:

[0023] S1.4, transferring the nanodiamond abrasive with the conductive hydrophilic coating into the coupling agent solution, stirring, filtering and drying in sequence;

[0024] S1.5, then transferring the dried nano-diamond abrasive to an electrostatic electret device, performing an electrostatic electret process, and slowly reducing the pressure and temperature after the electret process is completed to obtain a nano-diamond abrasive with a charge on the surface;

[0025] S1.6. Transferring the nano-diamond abrasive with a charge on the surface to an antistatic hydrophilic coating solution, heating and stirring, and then performing a deposition and pulling process, and after thermal curing, obtaining the nano-diamond abrasive with the surface layer.

[0026] In some embodiments of the present invention, in step S1.5, the antistatic hydrophilic coating solution includes at least one of polysulfobetaine, quaternary ammonium salt polymer, polyethylene glycol-modified polyurethane, and polyethylene glycol-modified polystyrene;

[0027] In step S1.6, the electric field strength is 10-25 kV / cm, the electret time is 10-30 min, the relative humidity of the environment is 30-50%, and the electret temperature is 20-25°C.

[0028] In some embodiments of the present invention, step S2 includes:

[0029] S2.1, adding a dispersant and a pH adjuster to a portion of a polar solvent to obtain a pre-solution;

[0030] S2.2, adding the nano-diamond abrasive into the pre-solution in batches, while stirring at high and low speeds alternately;

[0031] S2.3. Add the remaining polar solvent and stir to obtain a mixed solution.

[0032] In some embodiments of the present invention, step S3 includes:

[0033] S3.1, transfer the mixed solution into an ice bath container and then transfer it into an ultrasonic device for ultrasonic dispersion;

[0034] S3.2, filtering the mixed solution after ultrasonic dispersion;

[0035] S3.3. Add a suspending agent to the mixed solution after filtration, and perform ultrasonic dispersion again to obtain a pre-treatment solution.

[0036] Compared with the prior art, the pretreatment liquid and preparation method thereof applied to semiconductor substrates in the present invention have the following beneficial effects:

[0037] The conductive hydrophilic coating of nanodiamond particles forms a conductive coating on the surface of the nanoparticles, which improves the conductivity during the grinding process and reduces the accumulation of static electricity. Especially in the high-speed fine grinding process, reducing static electricity can prevent particle agglomeration and improve grinding accuracy and stability. The conductive hydrophilic coating also makes the particles more hydrophilic, improves their dispersibility and stability in the solution, and ensures the consistency of the liquid during processing.

[0038] Moreover, the pretreatment liquid optimizes the liquid formula by combining appropriate proportions of nano-diamond abrasives, dispersants, pH adjusters and suspending agents, so that it has a longer storage life and stability under different environments, is less prone to performance degradation, and reduces the need for frequent replacement of the pretreatment liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a schematic flow chart of a method for preparing a pre-treatment solution for a semiconductor substrate according to an embodiment of the present invention;

[0040] Figure 2 It is a partial flow diagram of a method for preparing a pretreatment solution applied to a semiconductor substrate in one embodiment of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] The present invention provides a pretreatment liquid applied to a semiconductor substrate, comprising: nano-diamond abrasive, a dispersant, a pH regulator, a suspending agent and a polar solvent. The nano-diamond abrasive is provided with a surface layer, and the surface layer comprises a conductive hydrophilic coating. Calculated by weight percentage, the nano-diamond abrasive accounts for 0.1-2%, the dispersant accounts for 1-5%, the pH regulator accounts for 0.5-2%, the suspending agent accounts for 0.5-3%, and the balance is the polar solvent.

[0043] The pretreatment liquid can effectively reduce the mechanical stress on the semiconductor substrate during the processing, reduce the generation of surface defects and microcracks on the substrate, and thus improve the quality and service life of the substrate material.

[0044] The extremely small particle size and surface coating of nano-diamond abrasives give them a higher surface contact area and uniform cutting effect, which can finely grind semiconductor substrates and reduce surface roughness. When using this pre-treatment liquid, the surface grinding accuracy of semiconductor substrates is higher and lower surface roughness can be achieved, thereby improving the quality of subsequent processing. The pre-treatment liquid optimizes the liquid formula by combining appropriate proportions of nano-diamond abrasives, dispersants, pH adjusters and suspending agents, so that it has a long storage life and stability in different environments, is not prone to performance degradation, and reduces the need for frequent replacement of pre-treatment liquids.

[0045] The conductive hydrophilic coating of nanodiamond particles forms a conductive coating on the surface of the nanoparticles, which improves the conductivity during the grinding process and reduces the accumulation of static electricity. Especially in the high-speed fine grinding process, reducing static electricity can prevent particle agglomeration and improve grinding accuracy and stability. The conductive hydrophilic coating also makes the particles more hydrophilic, improves their dispersibility and stability in the solution, and ensures the consistency of the liquid during processing.

[0046] The use of dispersants can effectively prevent the agglomeration of nanodiamond particles in the pretreatment solution, ensure that the particles are evenly dispersed in the solution, and enhance the dispersion stability of the abrasive. The dispersed nanodiamond particles can act more evenly on the semiconductor substrate, provide a more uniform grinding effect, reduce the unevenness during the processing, and improve the accuracy of surface treatment.

[0047] The addition of the suspending agent increases the viscosity of the liquid, preventing the nanodiamond particles from settling during storage and use, allowing the particles to be suspended in the solution for a long time, ensuring that the particles of the pre-treatment liquid are evenly distributed during use without stratification. Through suspension stability, the pre-treatment liquid can maintain its performance for a long time, reducing the need for cleaning and redispersion caused by particle sedimentation.

[0048] The use of pH adjusters maintains the pretreatment solution in an appropriate pH range (e.g., 6-8) to ensure the stability of the dispersant, suspending agent, and the surface chemistry of the nano-diamond particles. The appropriate pH value can prevent the agglomeration, oxidation, or chemical inactivation of the particles and maintain the stability of the liquid performance. pH adjustment can also protect the semiconductor substrate from corrosion and improve the compatibility of the pretreatment solution with the diamond material.

[0049] Specifically, the dispersant includes at least one of polyacrylic acid, polymaleic anhydride, acrylic acid / 2-propylene sulfonic acid copolymer, and polyacrylamide;

[0050] The pH regulator includes at least one of sodium hydroxide, potassium hydroxide, triethanolamine, and ammonia water;

[0051] The suspending agent includes at least one of hydroxyethyl cellulose, xanthan gum, carbomer and bentonite;

[0052] The polar solvent includes at least one of deionized water, ethanol, acetone and isopropanol.

[0053] Embodiment 1:

[0054] Please refer to Figure 1 In embodiment 1 of the present invention, a preparation method is proposed for preparing a pretreatment solution for a semiconductor substrate. The steps of the preparation method include:

[0055] S1. Pre-treating the nano-diamond raw material to obtain the nano-diamond abrasive.

[0056] Step S1 includes:

[0057] S1.1. Place the nano-diamond raw material in a plasma chamber, evacuate the chamber, introduce oxygen, and start the plasma excitation source for activation treatment. The oxygen flow rate is 30 sccm, the RF power is set to 150 W, the activation treatment time is 15 minutes, and the particle size of the nano-diamond raw material is 200 nm.

[0058] The plasma equipment includes a plasma chamber and a plasma excitation source, which are used to pass gas for plasma treatment. The plasma excitation source applies an electric field or a magnetic field to excite the gas into a plasma state through electrical energy.

[0059] The specific structure of the plasma equipment in the embodiments of the present invention is well known to those skilled in the art. The improvement of the present invention is mainly focused on the application of plasma treatment to the nano-diamond raw material. Through oxygen plasma activation treatment, oxygen-containing groups (such as hydroxyl, carboxyl, etc.) are introduced on the surface of the nano-diamond particles to increase the surface active groups. This can significantly enhance the ability of the particles to bind to the coating material, improve its adhesion to the hydrophilic conductive coating, and thus enhance the uniformity and firmness of the subsequent coating. The activation treatment can also remove organic pollutants on the surface of the particles, further improving the dispersion effect of the particles in the coating solution.

[0060] S1.2, transfer the activated nano-diamond raw material to an acid washing solution, and then wash, filter and dry in sequence to obtain surface-modified nano-diamond particles. The acid washing solution is a 1:1 mixture of nitric acid and hydrogen peroxide, and the mixture is soaked for 10 minutes.

[0061] The acid wash treatment can effectively remove metal ion residues and other impurities on the surface of nanodiamonds, further improving the purity of the particles. The washing, filtering and drying processes help ensure that there are no residual impurities and acid on the surface of the nanoparticles, ensuring the effectiveness of the subsequent coating process.

[0062] S1.3, transfer the surface modified nano-diamond particles to the conductive hydrophilic coating solution, heat and stir, and then perform a deposition and pulling process, and after drying and thermal curing, obtain a nano-diamond abrasive with a conductive hydrophilic coating. The conductive hydrophilic coating solution can be a 5% carboxylated polyvinyl pyrrolidone solution, stirred and heated to 60°C, and the stirring time is 1 hour.

[0063] The deposition pull process is a coating technology commonly used to deposit a uniform thin film on the surface of a substrate. It is done by immersing the substrate or particles in a coating solution and then pulling it out at a controlled speed so that the coating is evenly deposited on the surface. During the pulling process, ensure that the sample is perpendicular to the liquid surface and pulled at a constant speed to avoid uneven coating thickness. Set the pulling speed to 0.5-2mm / s to ensure that the coating is evenly coated on the particle surface.

[0064] The deposition and pulling equipment uses a tray to lift and lower the solution. The specific structure of the deposition and pulling equipment in the embodiment of the present invention is well known to those skilled in the art. The improvement of the present invention is mainly focused on the application of the deposition and pulling process to the nano-diamond raw material, so that the nano-diamond abrasive in the conductive hydrophilic coating solution is stirred and kept in a suspended state to attach the conductive hydrophilic coating.

[0065] Initial pulling (pulling after immersion), set the pulling speed to 1.5 mm / s to ensure the initial formation of a uniform film. Through feedback from the viscosity detector, when the solution viscosity gradually increases, the pulling speed is automatically reduced to 1 mm / s. When the solution approaches the top, the polar solvent evaporates rapidly, the viscosity continues to increase, and the pulling speed is reduced to 0.5 mm / s to prevent the liquid surface from being uneven or forming an overly thick coating.

[0066] The relationship between the pulling speed and coating thickness is: ;

[0067] in, is the coating thickness, is the impact factor, is the solution viscosity, is the pulling speed, It is the surface tension of the solution, which is determined experimentally. It is 0.1~1, for example, it can be 0.5, 0.8, etc.

[0068] After surface modification, nanodiamond particles can form a good combination with the conductive hydrophilic coating, making the particles have certain conductive properties and improving their dispersibility in the aqueous system. This coating not only improves the suspension stability of the particles, but also gives them a certain conductivity, which can effectively prevent static electricity accumulation during fine grinding and avoid particle agglomeration.

[0069] The coated nanodiamond particles have better dispersibility and anti-sedimentation properties in the solution. After the deposition and thermal curing process, the coating on the surface of the particles is uniform and stable, and can remain dispersed for a long time, making it suitable for high-precision semiconductor substrate processing.

[0070] S2. Adding the nano-diamond abrasive into a polar solvent containing a dispersant and a pH adjuster in batches to obtain a mixed solution.

[0071] Step S2 includes:

[0072] S2.1, adding a dispersant and a pH regulator to a portion of a polar solvent to obtain a pre-solution. The dispersant is polymaleic anhydride, accounting for 5% of the total mass, the pH regulator is sodium hydroxide, accounting for 1.5%, and deionized water is used as the polar solvent.

[0073] The performance and ionization state of dispersants are often dependent on the pH of the solution. Without pH adjustment, the dispersant may not be able to fully exert its dispersing ability. Therefore, mixing the dispersant with a pH adjuster and adjusting it to the appropriate pH value can ensure that the dispersant works at its optimal working state. The pH adjuster can help the dispersant dissolve better in polar solvents and control the charge distribution, allowing the dispersant to be fully activated before the nanoparticles are added, thereby providing a better dispersion environment for the nanoparticles.

[0074] If diamond abrasive is added directly to the dispersant solution without pH adjustment, the dispersant may not fully function, causing the particles to agglomerate. Mixing the dispersant and pH adjuster first can provide a stable dispersion environment for the diamond abrasive and prevent it from agglomerating when added.

[0075] S2.2, add nano-diamond abrasive to the pre-solution in batches, stirring alternately at high and low speeds. Add 20% of the nano-diamond abrasive each time, and stir to fully disperse it before adding the next batch, adding in 5 batches. After each addition, stir at a low speed of 300 rpm for 10 minutes to ensure that the particles are initially dispersed, then switch to high-speed stirring at 5000 rpm for 15 minutes.

[0076] By alternating between low-speed stirring and high-shear stirring, agglomeration can be prevented in the early stage while accelerating dispersion in the later stage. Alternating between the two stirring modes each time ensures the best dispersion effect. Low-speed stirring is used to gently mix the particles when they are first added to avoid rapid aggregation of particles and clusters caused by strong stirring. High-shear stirring is used to apply greater shear force to destroy particle aggregates after the particles are initially dispersed, so that the particles can be further dispersed and stably suspended in the solution. Monitor the temperature during the stirring process and place the sample in an ice water bath or cooling device to keep the temperature below 30°C.

[0077] S2.3. Add the remaining polar solvent and stir to obtain a mixed solution.

[0078] After the nanoparticles are fully dispersed, adding the remaining polar solvent helps adjust the concentration and viscosity of the solution so that the overall solution is evenly distributed. Adding polar solvent in stages can prevent particle aggregation or insufficient dispersion due to excessive polar solvent at one time. Adding polar solvent in stages can ensure the stability of the solution, prevent the problem of local over-concentration during the dispersion process, and maintain the uniformity and fluidity of the solution.

[0079] S3. Add a suspending agent to the mixed solution and perform ultrasonic dispersion to obtain a pre-treatment solution.

[0080] Step S3 includes:

[0081] S3.1. Transfer the mixed solution to an ice bath container and then to an ultrasonic device for ultrasonic dispersion. The ultrasonic frequency is 40 kHz, the ultrasonic power is set to 300 W, and the ultrasonic time is 20 min.

[0082] The specific structures of the ice bath container and ultrasonic equipment in the embodiments of the present invention are well known to those skilled in the art. The improvements of the present invention are mainly focused on the application of ultrasonic dispersion of nanodiamond raw materials. The mixed solution is placed in an ice bath and transferred to the ultrasonic equipment for ultrasonic dispersion. The main purpose is to prevent the heat generated by mechanical vibration and ultrasonic action during the ultrasonic process from causing the solution temperature to rise. High temperature may reduce the dispersion effect and may even cause the dispersant or other components in the solution to fail. The ice bath can stably control the solution temperature and keep it within an appropriate range (not exceeding 30°C) to ensure that the nanoparticles are evenly dispersed in a low temperature environment.

[0083] Ultrasonic dispersion can generate strong local shear force through cavitation effect, break up the aggregates between nanodiamond particles, and redisperse the particles in the solution. Compared with mechanical stirring, ultrasonic dispersion can more thoroughly break up fine aggregates, ensure uniform dispersion of particles, and improve the stability and dispersion effect of the pretreatment solution. In addition, ultrasonic dispersion can make the surface of nanoparticles fully contact with the dispersant in the solution, forming a stable particle suspension state and reducing the sedimentation or re-agglomeration of particles.

[0084] S3.2. Filter the mixed solution after ultrasonic dispersion.

[0085] After ultrasonic dispersion, the filtration step can effectively remove incompletely dispersed agglomerates, large particles or other impurities, ensuring that the particles in the mixed solution are uniform and the particle size meets the requirements. Removing large particles by filtration can improve the stability of the solution, prevent uneven grinding or surface defects in subsequent processing, and improve the purity and processing effect of the pre-treatment solution.

[0086] S3.3, add a suspending agent to the mixed solution after filtration, and perform ultrasonic dispersion again to obtain a pre-treatment solution. The suspending agent is hydroxyethyl cellulose, accounting for 3% of the total amount.

[0087] After filtration, the suspending agent is added. The suspending agent can effectively improve the viscosity and rheology of the pretreatment solution, prevent the particles from settling during storage or use, and ensure that the particles remain uniformly suspended in the solution for a long time. The addition of the suspending agent can prevent the nanodiamond particles from agglomerating in subsequent applications and improve the long-term stability of the pretreatment solution. Ultrasonic dispersion is performed again to fully mix the suspending agent with the solution and ensure that the suspending agent is evenly distributed throughout the solution, further improving the dispersion uniformity and suspension stability of the particles.

[0088] Embodiment 2:

[0089] Please refer to Figure 2 In embodiment 1 of the present invention, a preparation method is proposed for preparing a pretreatment solution for a semiconductor substrate. The steps of the preparation method include:

[0090] S1. Pre-treating the nano-diamond raw material to obtain the nano-diamond abrasive.

[0091] Step S1 includes:

[0092] S1.1. Place the nano-diamond raw material in a plasma chamber, evacuate the chamber, introduce oxygen, and start the plasma excitation source for activation treatment. The oxygen flow rate is 50 sccm, the RF power is set to 200 W, the activation treatment time is 20 min, and the particle size of the nano-diamond raw material is 300 nm.

[0093] S1.2, transfer the activated nano-diamond raw material to the pickling solution, and then wash, filter and dry in sequence to obtain surface-modified nano-diamond particles. The pickling solution is a 1:1 mixture of hydrochloric acid and hydrogen peroxide, and soak for 10 minutes.

[0094] S1.3, transferring the surface modified nano-diamond particles to the conductive hydrophilic coating solution, heating and stirring, and then performing a deposition and pulling process, and after drying and thermal curing, obtaining a nano-diamond abrasive with a conductive hydrophilic coating. The conductive hydrophilic coating solution can be 3% polyethylene glycol-modified polyaniline, stirred and heated to 60°C, and the stirring time is 1 hour.

[0095] S1.4, transferring the nano-diamond abrasive with the conductive hydrophilic coating to the coupling agent solution, stirring, filtering and drying in sequence. The coupling agent can be a silane coupling agent, such as γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane or γ-glycidyloxypropyl trimethoxysilane.

[0096] The coupling agent can effectively enhance the adhesion between the nanodiamond particles and the subsequent coating by forming a chemical bonding layer on the surface of the nanodiamond particles. This helps to ensure a stable bond between the antistatic hydrophilic coating and the conductive hydrophilic coating, preventing the coating from falling off or delaminating.

[0097] The use of coupling agents can reduce the surface energy of particles, further improve the dispersion of particles in liquids, and prevent agglomeration. Coupling agents can also form a bridge between particles and subsequent antistatic coatings, improving the hydrophilicity and chemical compatibility of the nanoparticle surface.

[0098] S1.5, then transfer the dried nano-diamond abrasive to the electrostatic electret device for electrostatic electret process, and slowly reduce the voltage and temperature after the electret process to obtain nano-diamond abrasive with surface charge. The electric field strength is 15 kV / cm, the electret time is 30 minutes, the relative humidity of the environment is 30%, and the electret temperature is 25°C.

[0099] The electrostatic charging process can keep the surface of nano-diamond particles with a persistent static charge. These charges can generate a stable charge repulsion between the particles, thereby avoiding mutual attraction and agglomeration of the particles in the pre-treatment solution. Especially in long-term use, the electrostatic repulsion imparted by the electret process can maintain good dispersion of the particles and prevent the particles from settling or agglomerating. The electrostatic repulsion brought by the electret process can also significantly improve the suspension stability of the particles in the pre-treatment solution. Through the electrostatic repulsion effect, the particles can remain evenly dispersed for a long time and are not easy to settle, which is crucial to ensure the long-term service life and stability of the pre-treatment solution.

[0100] During high-speed rotation or friction, the nanoparticles in the pretreatment fluid are prone to electrostatic accumulation due to frictional charging. The surface of the particles after electret treatment already has a persistent charge, which can play a role in static dissipation during the processing, preventing static electricity accumulation from interfering with the grinding effect and improving the overall processing accuracy and stability.

[0101] S1.6, transfer the nano-diamond abrasive with a charge on the surface to an antistatic hydrophilic coating solution, heat and stir, and then perform a deposition and pulling process, and after thermal curing, obtain a nano-diamond abrasive with a surface layer. The antistatic hydrophilic coating solution is 5% polysulfobetaine.

[0102] The main function of the antistatic hydrophilic coating is to dissipate static electricity and prevent static electricity accumulation. After being coated with the antistatic coating, the nano diamond particles not only have a stable electret charge, but also can prevent static electricity accumulation in the external environment. This is especially important in high-load, high-friction processing environments. The antistatic coating can protect the particles from external static electricity and maintain the stability of the grinding process.

[0103] Although the charge brought by the electrostatic charging process helps disperse the particles, excessive charge may also cause excessive adsorption between the particles and other components in the grinding fluid. Antistatic coating can properly dissipate excessive static charge, prevent the adsorption effect of particles caused by excessive charge, and ensure the stable performance of the pre-treatment fluid.

[0104] Antistatic coating can also enhance the hydrophilicity of particles, further enhancing the compatibility of particles with aqueous polar solvents, ensuring that the pretreatment solution maintains good fluidity and stability during long-term use. This feature can reduce particle deposition and fluidity loss during high-precision processing, and improve the finish of the processed surface.

[0105] Through the double-layer protection of conductive hydrophilic coating and antistatic hydrophilic coating, as well as the electrostatic repulsion imparted by the electrostatic electret process, the nano-diamond abrasive can remain stably dispersed in the pre-treatment liquid for a long time, avoiding agglomeration or sedimentation, and improving the service life and performance of the pre-treatment liquid.

[0106] The outer layer of antistatic hydrophilic coating can minimize the problem of particle adsorption caused by static electricity. The outer coating is in direct contact with the outside world, which can quickly dissipate the charge, reduce the pollution caused by surface static electricity, and improve the quality of surface treatment in the process. At the same time, with the long-term use of nano-diamond abrasives, when the outer antistatic coating is partially detached or worn, the inner conductive coating will gradually be exposed to the external environment, which plays a role in continuously improving the dispersion. In addition, the nano-diamond abrasive with an unworn antistatic coating and the nano-diamond abrasive with a conductive coating have different charge effects in the fine grinding liquid, and the two repel each other and inhibit the occurrence of agglomeration, thereby improving the overall dispersion.

[0107] S2. Adding the nano-diamond abrasive into a polar solvent containing a dispersant and a pH adjuster in batches to obtain a mixed solution.

[0108] Step S2 includes:

[0109] S2.1, adding a dispersant and a pH regulator to a portion of a polar solvent to obtain a pre-solution. The dispersant is acrylic acid / 2-propylene sulfonic acid copolymer, accounting for 3% of the total mass, the pH regulator is potassium hydroxide, accounting for 2%, and deionized water is used as the polar solvent.

[0110] S2.2, add nano-diamond abrasive to the pre-solution in batches, stirring alternately at high and low speeds. Add 20% of the nano-diamond abrasive each time, and stir to fully disperse it before adding the next batch, adding in 5 batches. After each addition, stir at a low speed of 300 rpm for 10 minutes to ensure that the particles are initially dispersed, then switch to high-speed stirring at 5000 rpm for 15 minutes.

[0111] S2.3. Add the remaining polar solvent and stir to obtain a mixed solution.

[0112] S3. Add a suspending agent to the mixed solution and perform ultrasonic dispersion to obtain a pre-treatment solution.

[0113] Step S3 includes:

[0114] S3.1. Transfer the mixed solution to an ice bath container and then to an ultrasonic device for ultrasonic dispersion. The ultrasonic frequency is 40 kHz, the ultrasonic power is set to 300 W, and the ultrasonic time is 20 min.

[0115] S3.2. Filter the mixed solution after ultrasonic dispersion.

[0116] S3.3, add a suspending agent to the mixed solution after filtration, and perform ultrasonic dispersion again to obtain a pre-treatment solution. The suspending agent is xanthan gum, accounting for 3% of the total amount.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A pretreatment solution for a semiconductor substrate, characterized in that: include: Nano-diamond abrasive, dispersant, pH regulator, suspending agent and polar solvent, wherein the nano-diamond abrasive is provided with a surface layer, the surface layer comprises a conductive hydrophilic coating and an antistatic hydrophilic coating provided on the surface of the conductive hydrophilic coating, and calculated by weight percentage, the nano-diamond abrasive accounts for 0.1-2%, the dispersant accounts for 1-5%, the pH regulator accounts for 0.5-2%, the suspending agent accounts for 0.5-3%, and the balance is the polar solvent; The preparation method of the pretreatment solution comprises: S1, pretreating the nano-diamond raw material to obtain a nano-diamond abrasive; Step S1 includes: S1.

1. Place the nanodiamond raw material in a plasma chamber, evacuate the chamber, introduce oxygen, and start the plasma excitation source for activation treatment; S1.2, transferring the activated nanodiamond raw material to an acid washing solution, and then washing, filtering and drying in sequence to obtain surface-modified nanodiamond particles; S1.3, transferring the surface modified nano-diamond particles into a conductive hydrophilic coating solution, heating and stirring, and then performing a deposition and pulling process, and after drying and thermal curing, obtaining a nano-diamond abrasive with a conductive hydrophilic coating; S1.4, transferring the nanodiamond abrasive with the conductive hydrophilic coating into the coupling agent solution, stirring, filtering and drying in sequence; S1.5, then transferring the dried nano-diamond abrasive to an electrostatic electret device, performing an electrostatic electret process, and slowly reducing the pressure and temperature after the electret process is completed to obtain a nano-diamond abrasive with a charge on the surface; S1.6, transferring the nano-diamond abrasive with a charge on the surface to an antistatic hydrophilic coating solution, heating and stirring, and then performing a deposition and pulling process, and after thermal curing, obtaining a nano-diamond abrasive with the surface layer; S2, adding the nano-diamond abrasive into a polar solvent containing a dispersant and a pH adjuster in batches to obtain a mixed solution; S3. Add a suspending agent to the mixed solution and perform ultrasonic dispersion to obtain a pre-treatment solution.

2. The pretreatment solution for semiconductor substrate according to claim 1, characterized in that: The dispersant includes at least one of polymaleic anhydride, acrylic acid / 2-propylene sulfonic acid copolymer, and polyacrylamide; The pH regulator includes at least one of sodium hydroxide, potassium hydroxide, triethanolamine, and ammonia water; The suspending agent includes at least one of hydroxyethyl cellulose, xanthan gum, carbomer and bentonite; The polar solvent includes at least one of deionized water, ethanol, acetone and isopropanol.

3. The pretreatment solution for semiconductor substrate according to claim 1, characterized in that: In the step S1.1, the oxygen flow rate is 20-50 sccm; In the step S1.2, the pickling solution includes a strong acid and hydrogen peroxide, the strong acid includes at least one of sulfuric acid, nitric acid, and hydrochloric acid, and the volume ratio of the strong acid to the hydrogen peroxide is 1:1-2; In the step S1.3, the conductive hydrophilic coating solution includes at least one of carboxylated polyvinyl pyrrolidone, polyethylene glycol-modified polyaniline, and polyethylene glycol-modified polypyrrole.

4. The pretreatment solution for semiconductor substrate according to claim 1, characterized in that: In the step S1.5, the antistatic hydrophilic coating solution includes at least one of polysulfobetaine, quaternary ammonium salt polymer, polyethylene glycol-modified polyurethane, and polyethylene glycol-modified polystyrene; In step S1.6, the electric field strength is 10-25 kV / cm, the electret time is 10-30 min, the relative humidity of the environment is 30-50%, and the electret temperature is 20-25°C.

5. The pretreatment solution for semiconductor substrate according to claim 1, characterized in that: The step S2 comprises: S2.1, adding a dispersant and a pH adjuster to a portion of a polar solvent to obtain a pre-solution; S2.2, adding the nano-diamond abrasive into the pre-solution in batches, while stirring at high and low speeds alternately; S2.

3. Add the remaining polar solvent and stir to obtain a mixed solution.

6. The pretreatment solution for semiconductor substrate according to claim 1, characterized in that: The step S3 comprises: S3.1, transfer the mixed solution into an ice bath container and then transfer it into an ultrasonic device for ultrasonic dispersion; S3.2, filtering the mixed solution after ultrasonic dispersion; S3.

3. Add a suspending agent to the mixed solution after filtration, and perform ultrasonic dispersion again to obtain a pre-treatment solution.

Citation Information

Patent Citations

  • High-precision non-water-based nano-diamond grinding fluid and preparation method and application thereof

    CN101831243A

  • Diamond surface modification method and application

    CN112030145A

  • Nano-diamond polishing solution for SiC substrate processing and preparation method thereof

    CN112592663A

  • Composition for chemical-mechanical polishing and method of using same

    US20050014890A1

  • Method for Electrostatically Scattering an Abrasive Grain

    US20190366511A1